The Mimicry of Shia Youths in Islamic ‎Education and Religious Space of Education ‎Institutions - Ardiansyah, Mochammad Zaka (TADRIS: Jurnal Pendidikan Islam, 2022)
This article aims to reveal the discriminatory experiences encountered by Shia youths in educational institutions and their strategies for constructing their identities, both in Islamic religious education classes and in the public spaces of educational institutions. This article is the result of a qualitative-descriptive study of five Shia youths in Jember who were recruited using the chain-referral sampling method. Data collected by life-story interviews were analyzed using interactive model (Miles, et al). This article finds that Shia youths encounter discriminatory experiences because they are required by Islamic Religious Education teachers to recite prayers such as qunut, even though they claim to be members of Muhammadiyah. The two Shia youths who imitated members of Muhammadiyah intended to avoid the practice of Nahdlatul Ulama-style prayers preferred by their Islamic Religious Education teachers. In addition, Shia youth generally do not dare to reveal their identity as adherents of Shia. A Shia youth claims to be a traditional Muslim or follower of Islam to avoid discrimination from his friends. It was also dicovered that Shia youths pretend to perform prayers according to the Sunni schools while secretly performing Shia prayers to fight for their right to worship. Mimicry performed by minority Shia youths confirms Homi K. Bhabha's image of mimicry because Shia youths use the Sunni Muslim's identity space. However, they secretly try to maintain their primordial identity as Shias so that minority Shia youths use an identity that is almost the same as that of Sunni Muslim, “but not completely the same”.